The Artist and the Bridge : 1700-1920. - Sweetman, John. (Oxford : Taylor & Francis Group, 2019)
First published in 1999, this book explores how, from the stone bridges of neoclassicism which soar out of wild woods to span pastoral valleys to the post-1750 engineer's bridge with its links to the more industrial landscape, the bridge was a popular feature in painting throughout the period 1700-1920.
Cover -- Half Title -- Title Page -- Copyright Page -- Contents -- List of illustrations -- Acknowledgements -- Preface -- Introduction: The approaches -- 1 Views and sightlines 1700-1800 -- Figures 12-30 -- 2 New encounters, new effects 1750-1800 -- Figures 31-46 -- 3 Far objectives, missed connexions 1800-1850 -- Figures 47-67 -- 4 Realities and ideals 1800-1920 -- Figures 68-104 -- Bibliographical notes -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Symbolism in art; Electronic books